2017
DOI: 10.1002/2017gl074748
|View full text |Cite
|
Sign up to set email alerts
|

Summer drought reconstruction in northeastern Spain inferred from a tree ring latewood network since 1734

Abstract: Drought recurrence in the Mediterranean is regarded as a fundamental factor for socioeconomic development and the resilience of natural systems in context of global change. However, knowledge of past droughts has been hampered by the absence of high‐resolution proxies. We present a drought reconstruction for the northeast of the Iberian Peninsula based on a new dendrochronology network considering the Standardized Evapotranspiration Precipitation Index (SPEI). A total of 774 latewood width series from 387 tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(24 citation statements)
references
References 84 publications
1
19
0
4
Order By: Relevance
“…Numerous studies have shown that the intensity and frequency of drought events have increased owing to rapid climate warming (IPCC, 2013;Trenberth et al, 2014). Droughts have serious adverse effects on social, natural, and economic systems (Ficklin et al, 2015;Yao and Chen, 2015;Tejedor et al, 2017;Yu et al, 2018). Globally, drought is considered to be the most destructive climate-related disaster, and it has caused billions of dollars in worldwide loss (van der Schrier et al, 2013;Lesk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the intensity and frequency of drought events have increased owing to rapid climate warming (IPCC, 2013;Trenberth et al, 2014). Droughts have serious adverse effects on social, natural, and economic systems (Ficklin et al, 2015;Yao and Chen, 2015;Tejedor et al, 2017;Yu et al, 2018). Globally, drought is considered to be the most destructive climate-related disaster, and it has caused billions of dollars in worldwide loss (van der Schrier et al, 2013;Lesk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Drought is one of the main climatic risks affecting Spain, with drastic impacts on both natural and human environments (Vicente‐Serrano et al, ). Several historical drought episodes in Spain have already been identified either in documentary sources (e.g., Vicente Serrano and Cuadrat, ; Domínguez‐Castro et al, , ) or from dendrochronological records (e.g., Tejedor et al, , ). The available long instrumental data covering the entire 20th century suggests an increase in the frequency and severity of drought episodes across Iberia (Vicente‐Serrano, and ).…”
Section: Introductionmentioning
confidence: 99%
“…En España: Robson, Rasztovits, Aphalo, Alia y Aranda, 2013Martínez del Castillo et al, 2016), donde se establece un periodo de máxima actividad cambial entre abril y julio, para reducirse rápidamente a partir de ahí. Este patrón confirma la dinámica de crecimiento sensible a la sequía, tanto primaveral como estival, ampliamente apoyada por la literatura a lo largo del área de distribución natural de Fagus sylvatica en toda Europa (Dittmar et al, 2003;Tegel et al, 2014); en España (Rozas, 2001; Reconstrucción dendroclimática de la serie de precipitaciones en el Valle de Polaciones (Cantabria) 2006; Rozas et al, 2015;Jump, et al, 2006Jump, et al, , 2007Peñuelas, Ogaya, Boada, Jump, 2007;Tejedor, De Luis, Cuadrat, Esper y Saz, 2016;Tejedor, Saz, Esper, Cuadrat, & Luis, 2017); en Italia (Piovesan et al, 2005a); Francia (Lebourgeois, Breda, Ulrich y Granier, 2005;Michelot et al, 2012a); Alemania (Friedrichs et al, 2009;Scharnweber et al, 2011) o Suecia (Drobyshev et al, 2010).…”
Section: Discusión De Resultadosunclassified